Doubles trouble - 85 cases of ocular trauma in badminton: clinical features and prevention - Yu, J.; Chen, Y.; Miao, J.; Zhao, M.; Keng, C.; Wang, X.; Guo, J.; Liu, Y. (British Journal of Sports Medicine, 2020)
Objectives: To describe ocular injuries caused by badminton and to explore the implications for future prevention strategies.